2010
DOI: 10.2341/09-038cr1
|View full text |Cite
|
Sign up to set email alerts
|

Pulp Capping with Mineral Trioxide Aggregate (MTA): A Retrospective Analysis of Carious Pulp Exposures Treated by Undergraduate Dental Students

Abstract: ©Operative Dentistry, 2010, 35-1, 20-28 JP Miles • AH Gluskin D Chambers • OA Peters Clinical RelevanceCarious pulp exposures present a therapeutic challenge for clinicians. Mineral trioxide aggregate (MTA) is a treatment option that may provide successful outcomes for the capping of carious pulp exposures in adult patients. However, the success measured as pulp survival over a period of one and two years of pulp caps performed by undergraduate dental students may be low. This study provides data regarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…In a clinical trial, a lower success rate of 56.2% was reported after direct pulp capping with MTA (19). However, no attempt was made to fully remove carious dentin as soon as pulpal bleeding was observed.…”
Section: Clinical Researchmentioning
confidence: 92%
“…In a clinical trial, a lower success rate of 56.2% was reported after direct pulp capping with MTA (19). However, no attempt was made to fully remove carious dentin as soon as pulpal bleeding was observed.…”
Section: Clinical Researchmentioning
confidence: 92%
“…Only calcium hydroxide or MTA was used as medicament for vital pulp therapy. Articles were excluded for the following reasons: non-carious exposed teeth studies that mostly were trauma studies (55-57); inadequate clinical or radiograph examination (10, 58); success rate was not stated or could not be recalculated (52,59); calcium hydroxide or MTA was not used as pulp capping materials (60,61). Statistical comparison of the success rates among direct pulp capping, partial pulpotomy, and full pulpotomy might not be appropriate for various reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Another case series study, restricted to adults who were at least 18 years of age, demonstrated a comparatively low success rate (56%) for direct pulp capping using MTA after a 2‐year follow‐up (Miles et al . ).…”
Section: Introductionmentioning
confidence: 97%